INTRODUCTION TO THE SPECIAL ISSUE ON THE RIGHT TO EDUCATION - Bourne, John R.; Moore, Janet C.; SchWeber, Claudine (Online Learning, 2008)
n the 60 years since the Declaration, changes have swept higher education. The emergence of online education promises that growth in its quality, scale and breadth could insure that education becomes a right. Sloan-C research abundantly demonstrates that online education is effective for learning, especially for encouraging reflection, interaction, diversity and collaboration. It can take advantage of cost efficiencies, especially through curriculum redesign and shared resources. It provides access to more learners and more kinds of learners at their own chosen times and places. Although teaching and learning online may take more time and effort, the growth of online education in the United States to 20% of the entire college population shows that faculty and students readily engage online. Nevertheless, there is still tremendous potential for growth.